Analisis Kepatuhan Pajak Penghasilan Badan PT Quadra Mitra Perkasa - Nuriyan Nur Riyan; Yunus Tete Konde; Muhammad Abadan Syakura (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
ABSTRACT                Nuriyan, Compliance Analysis of Income Tax (PPh) of PT Quadra Mitra Perkasa, under the guidance of Mr. Yunus Tete Konde as Counselor I and Mr. Muhammad Abadan Syakura as counselor II               The purpose of this study was to determine the compliance of PT Quadra Mitra Perkasa Samarinda in carrying out the obligation to pay year-end corporate income tax (PPh) in accordance with applicable laws. The analytical tool used to determine income tax compliance is to use the laws of Law Number 28 of 2007, and regulations of the Taxation Law of the Republic of Indonesia Number 36 of 2008.            Based on the results of research conducted at PT Quadra Mitra Perkasa in reporting corporate income tax income has been carried out but not in accordance with the regulations that apply to Law No. 28 of 2007, namely the financial statements were not audited by public accountants in 2015 and 2016, so according to Law Number 28 of 2007, classified as non-compliant, and the calculation of the 2015 and 2016 Annual SPT that adjusts to Law No. 36/2008 that there are items in the income statement at PT Quadra Mitra Perkasa that are not appropriate , so that Fiscal reconciliation is needed in 2015 and 2016, Some of the uncorrected accounts are entertainment costs and representation and Article 21 Income Tax items.